Green algae chlorella vulgaris cultivation in municipal wastewater and biomass composition - Venckus, Petras; Kostkevičienė, Jolanta; Bendikienė, Vida (Journal of Environmental Engineering and Landscape Management, 2017)
This paper deals with the accumulation of lipids, carbohydrates and proteins in the biomass of the green algae Chlorella vulgaris that is cultivated in the municipal wastewater of Vilnius City. The growth rate of the culture on different chemical compositions of media was investigated. Dependence of lipid, carbohydrate and protein content on total phosphorus and nitrogen initial concentrations in wastewater and removal of nutrients was investigated. Data showed that the higher amount of total nitrogen is the main factor leading to a higher rate of biomass increase. The study showed that Chlorella vulgaris is capable of very efficient nutrient removal from wastewater (up to 86% of total nitrogen and 87% phosphorus was removed). Data showed that there is strong correlation between the initial concentration of nitrogen, and in some cases phosphorus, in the media and content of proteins and carbohydrates in the biomass. A higher amount of nitrogen in the starting media leads to a higher amount of proteins and a lower amount of carbohydrate in the biomass. There was no correlation found between the initial nitrogen or phosphorus concentration in the media and content of lipids in the biomass.